Benito Maresca: formação e trajetória profissional - Gomes, Simone Luiz (2009)
The first objective of the research is to investigate the musical, formal and not formal formation, and the evolution of the career of the lyric singer and professor Benito Maresca. For in such a way, I searched to characterize the difficulties found for Benito Maresca, when pledging itself in finding a professor who could take care of to its necessities, and the way trod in the search of the professional success, as singer and as professor. It is not difficult to evidence that the majority of the students of I sing lyric passes for some type of difficulty, when the choice of an adequate professor. They are of a very great variety the types of obstacles that a pupil can come across itself. Most common, perhaps, the problems of personal relationship or shunting line in the vocal classification say respect. The professors of I sing lyric are, in general, singers, who when locking up its careers, if become vocal people who orientates e, therefore, nor always exists a pedagogia that has as base used vocal techniques. The adopted metodológico procedure, as well as the one of the collection of data, was of the documentary analysis, that involved writings of depositions, for the proper singer, and periodical rescue and magazines on the professional career of Benito Maresca, in the period understood between years 60 and 90 of Brazil and the Europe. Benito Maresca executed innumerable workmanships of different composers, but always it was dedicated to the repertoire of the Romantic period, since its voice if adjusted better to this repertoire. For this, if it dedicates, still today, to the education of the practical one of I sing lyric, it directs and it guides diverse pupils who, as it, has prominence in the national and international lyric scene.